2011
DOI: 10.2139/ssrn.1312091
|View full text |Cite
|
Sign up to set email alerts
|

How Much Do Investors Care About Macroeconomic Risk? Evidence from Scheduled Economic Announcements

Abstract: Stock market average returns and Sharpe ratios are significantly higher on days when important macroeconomic news about inflation, unemployment, or interest rates is scheduled for announcement. The average announcement-day excess return from 1958 to 2009 is 11.4 basis points (bp) versus 1.1 bp for all the other days, suggesting that over 60% of the cumulative annual equity risk premium is earned on announcement days. The Sharpe ratio is 10 times higher. In contrast, the risk-free rate is detectably lower on an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
58
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(66 citation statements)
references
References 54 publications
(23 reference statements)
8
58
0
Order By: Relevance
“…The results in Table 1 extend the evidence documented by Savor and Wilson (2013) and Lucca and Moench (2014). In both studies, the authors examine whether the information contained in announcements affects the market returns on FOMC days by controlling for the surprises in time-series regressions of the market returns on indicators for FOMC days.…”
Section: Aggregate Market Returns On Fomc Meeting Dayssupporting
confidence: 69%
See 2 more Smart Citations
“…The results in Table 1 extend the evidence documented by Savor and Wilson (2013) and Lucca and Moench (2014). In both studies, the authors examine whether the information contained in announcements affects the market returns on FOMC days by controlling for the surprises in time-series regressions of the market returns on indicators for FOMC days.…”
Section: Aggregate Market Returns On Fomc Meeting Dayssupporting
confidence: 69%
“…The table re-ports results from time-series regressions of daily market excess returns on a constant and indicators for different types of FOMC days. The first specification closely resembles the result documented in Savor and Wilson (2013). On days with scheduled FOMC meetings, the market excess returns are 20 basis points higher than on all other days.…”
Section: Aggregate Market Returns On Fomc Meeting Dayssupporting
confidence: 63%
See 1 more Smart Citation
“…Major news announcements made by the Central banks of various nations or policy changes affecting the inflation rates and other economic parameters would have a significant impact on the financial markets. Savor and [6] observed that the average returns of the US financial stock markets were performing higher on those days where macroeconomic variables were declared to the public. These factors include consumer price index, employment rate and statistics, decisions made by Federal committee on financial markets among others.…”
Section: Background To Studymentioning
confidence: 99%
“…Jubinski and Tomljanovich (2013) and Savor and Wilson (2013), for example, examine return effects due to macro impacts, but to the best of our knowledge there is no study directly investigating the consequences of ECB announcements on the bid-ask spread using intraday data. Considering the 4 effects of major announcements as highly important in the context of stock market pricing, we analyze the impact of both interest rate decisions and press conferences by the ECB.…”
Section: Introductionmentioning
confidence: 99%